Gonadal vein leiomyosarcoma, from clinical practice to a literature review: surgical, oncological and histopathologic correlation - Imbriani, Giusy Carmen; Guarro, Giuseppe; Di Somma, Massimo Dante; Sarno, Italo; Ardito, Raffaele; Botte, Manuela; Fabrizio, Tommaso; Scala, Dario (Acta Biomedica Atenei Parmensis, 2023)
Background and aim:Vascular leiomyosarcomas are rare and generally originate from the muscular wall of the inferior vena cava. Leiomyosarcomas originating from the wall of the gonadal veins are rare and just about ten cases are described in literature. In the present paper, we have described a case of a LMS originating from the left gonadal vein.Methods:A 44-year-old woman presented in March 2020 pain symptoms at the level of the left renal lodge. The subsequent CT and the biopsy confirmed the diagnosis of G2 grade LMS. The mass was then removed en bloc from the posterior and inferior pancreatic plane, from the aortic plane and from the retroperitoneal plane, post chemoteraphy.Results:Pathologic report revealed a typical leiomyosarcoma, moderately differentiated G2 with minor dedifferentiated areas of pleomorphic leiomyosarcoma.Conclusions:The LMSs originating from gonadal veins represent an uncommon oncologic challenge. The radical en bloc excision represents the therapeutic gold standard.